2019
DOI: 10.1097/corr.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Gut Microbiome Increases the Risk of Periprosthetic Joint Infection in Mice

Abstract: Background Periprosthetic joint infection (PJI) is one of the most devastating complications of total joint arthroplasty. Given the mortality and morbidity associated with PJI and the challenges in treating it, there has been increased interest in risk factors that can be modified before surgery. In this study, we used a novel mouse model to consider the role of the gut microbiome as a risk factor for PJI. Questions/purposes (1) Does the state of the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 49 publications
1
56
0
Order By: Relevance
“…Cells were then fixed and permeabilized with Cytofix (BD) and then labeled with antibodies against intracellular IgG (catalog number 405308) to detect intracellular IgG that are high in plasma cells (15). Gating strategies are based on our previously published work (1,11,15). While the use of intracellular staining precluded the use of DAPI to assess dead cells, parallel samples that were not fixed, but were labeled with CD45 (catalog number 103127) and DAPI (catalog number 422801) demonstrated that 95% of tendon and lymph node CD45 + cells were DAPI -, indicating that they were viable cells.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Cells were then fixed and permeabilized with Cytofix (BD) and then labeled with antibodies against intracellular IgG (catalog number 405308) to detect intracellular IgG that are high in plasma cells (15). Gating strategies are based on our previously published work (1,11,15). While the use of intracellular staining precluded the use of DAPI to assess dead cells, parallel samples that were not fixed, but were labeled with CD45 (catalog number 103127) and DAPI (catalog number 422801) demonstrated that 95% of tendon and lymph node CD45 + cells were DAPI -, indicating that they were viable cells.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…The answer is yes. In a recent preclinical study, we showed that susceptibility to PJI was increased by almost 50% in mice with a disrupted gut microbiome community 24 (Figure 2A). Furthermore, those mice with a disrupted gut microbial community that went on to develop PJI showed a reduced systemic immune response to infection (measured by serum markers and immune cell populations in the spleen).…”
Section: Can the Microbiome Help Prevent Periprosthetic Joint Infectimentioning
confidence: 87%
“…Muscle mass and function are also influenced by the gut microbiota; a recent study found that germ‐free mice display muscle atrophy, a condition that can be reversed through the transfer of normal gut microbiota 21 . Additionally, recent studies have suggested that the presurgical state of the patient's gut microbiome can influence the success of gastrointestinal surgeries, 22,23 and has recently been shown to influence the success of orthopedic surgery in animals 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An antibiotic-induced minor change in the microbiome may increase the risk for an infection and postoperative DBJI. 79 …”
Section: Bone: a Waste Dump That Affects Healthmentioning
confidence: 99%